A dangerous business - Smiley, Jane (Alfred A. Knopf, 2022)
"From the beloved Pulitzer Prize-winning and best-selling author: a rollicking murder mystery set in Gold Rush California, as two young prostitutes follow a trail of missing girls. Monterey, 1851. Ever since her husband was killed in a bar fight, Eliza Ripple has been working in a brothel. It seems like a better life, at least at first. The madam, Mrs. Parks, is kind, the men are (relatively) well behaved, and Eliza has attained what few women have: financial security. But when the dead bodies of young women start appearing outside of town, a darkness descends that she can't resist confronting. Side by side with her friend Jean, and inspired by her reading, especially by Edgar Allan Poe's detective, Dupin, Eliza pieces together an array of clues to try to catch the killer, all the while juggling clients who begin to seem more and more suspicious. Eliza and Jean are determined not just to survive but to find their way in a lawless town on the fringes of the Wild West-a bewitching combination of beauty and danger-as what will become the Civil War looms on the horizon. As Mrs. Parks says, 'Everyone knows that this is a dangerous business, but between you and me, being a woman is a dangerous business, and don't let anyone tell you otherwise . . . '"--